Single‐domain antibodies targeting antithrombin reduce bleeding in hemophilic mice with or without inhibitors. Issue 4 (11th March 2020) - Barbon, Elena; Ayme, Gabriel; Mohamadi, Amel; Ottavi, Jean‐François; Kawecki, Charlotte; Casari, Caterina; Verhenne, Sebastien; Marmier, Solenne; van Wittenberghe, Laetitia; Charles, Severine; Collaud, Fanny; Denis, Cecile V; et al.
Abstract: Novel therapies for hemophilia, including non‐factor replacement and in vivo gene therapy, are showing promising results in the clinic, including for patients having a history of inhibitor development. Here, we propose a novel therapeutic approach for hemophilia based on llama‐derived single‐domain antibody fragments (sdAbs) able to restore hemostasis by inhibiting the antithrombin (AT) anticoagulant pathway. We demonstrated that sdAbs engineered in multivalent conformations were able to block efficiently AT activity in vitro, restoring the thrombin generation potential in FVIII‐deficient plasma. When delivered as a protein to hemophilia A mice, a selected bi‐paratopic sdAb significantly reduced the blood loss in a model of acute bleeding injury. We then packaged this sdAb in a hepatotropic AAV8 vector and tested its safety and efficacy profile in hemophilic mouse models. We show that the long‐term expression of the bi‐paratopic sdAb in the liver is safe and poorly immunogenic, and results in sustained correction of the bleeding phenotype in hemophilia A and B mice, even in the presence of inhibitory antibodies to the therapeutic clotting factor. Synopsis: This study presents a novel therapeutic approach for hemophilia A and B, with and without inhibitors. By using single‐domain antibodies targeting the anticoagulant antithrombin, a sustained correction of the in vivo bleeding phenotype was achieved following protein or AAV8‐based gene therapy. Bi‐paratopic single domain antibodies (sdAbs) have been generated that neutralized the anticoagulant protein antithrombin. Neutralization of antithrombin normalized thrombin generation in hemophilic plasma, irrespective of the presence of inhibitory antibodies. Liver expression of a bivalent sdAb restored clotting in hemophilia A and in hemophilia B mice, even in the presence of anti‐FIX antibodies. Abstract : This study presents a novel therapeutic approach for hemophilia A and B, with and without inhibitors. By using single‐domain antibodies targeting the anticoagulant antithrombin, a sustained correction of the in vivo bleeding phenotype was achieved following protein or AAV8‐based gene therapy.